Risk factors and clinical outcome of hypomagnesemic patients in pediatric intensive care - N., Poornima Shankar; C., Kavya; Reddy, Varsha Monica (International Journal of Contemporary Pediatrics, 2020)
Background: Hypomagnesemia is a common finding in current medical practice, especially in critically ill patients. Magnesium ion plays a vital role in various metabolic processes in body and its deficiency leading to serious clinical consequences. Since hypomagnesemia is most often asymptomatic, it goes unsuspected and therefore undiagnosed. Hence, early detection of hypomagnesemia has prognostic and therapeutic implications. It is imperative to understand the various risk factors and their clinical outcome that is associated with hypomagnesemia. Methods: This is an observational study done in a tertiary centre in Bangalore, India where-in 100 children who met the inclusion criteria, admitted to the PICU were recruited and prospectively studied. Serum Magnesium along with various clinical and biochemical parameters were correlated to enumerate the various risk factors associated with hypomagnesemia. Results: In this study authors found the incidence of hypomagnesemia to be around 53%. Authors found higher incidence in age group of 1-5 yrs (40%) and least were in the age groups of <1 year and more than 10 years (19%) and there was no gender preponderance. Authors also evaluated the various risk factors associated with hypomagnesemia. There was significant association of hypocalcemia (60%) and hypokalemia (45.2%) with hypomagnesemia. Infections (33.9%) and neurological disorders (26.41%) seemed to collectively comprise around 60% of the hypomagnesemic group. All patients admitted secondary to sepsis and Traumatic Brain Injury (TBI) had hypomagnesemia proving to be a significant risk factor. Authors also found increased mortality among hypomagnesemic group. However, found no association between low serum magnesium and PICU stay. Conclusions: There is high prevalence of hypomagnesemia in critically ill patients and is associated with a higher mortality. It is also commonly associated with infections, CNS disorders, respiratory diseases and metabolic derangements like hypokalaemia and hypocalcaemia. There is no association of Hypomagnesemia with duration of PICU stay.